FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESESUAIAN PRAKTIK GIZI PADA LANSIA BERDASARKAN 10 PESAN GIZI SEIMBANG (Studi di Kelurahan Sambiroto Kota Semarang) - Afra Dhiya Fadillah; Suyatno Suyatno; Sri Achadi Nugraheni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
There has been an increase in the number of the elderly and there are nutritional problems in elderly, which is malnutrition, so in order the elderly can maintain their health, it is necessary to do nutrition practices based on the Guidelines for Balanced Nutrition. The purpose of this study was to analyze the factors related to the suitability of nutrition practices in the elderly based on 10 Balanced Nutrition Messages in the Sambiroto District, Semarang City. Research conducted using a cross sectional design and consecutive sampling techniques, sample of this research were 103 respondents. For bivariate analysis using the Spearman rank correlation test, except gender variables using Chi-Square and for multivariate analysis using multiple linear regression test. The results showed that there are relationships between age (p = 0,005), length of education (p = 0,003), family income per capita (p = 0,034), accessibility to food (p = 0,018), the active role of health workers (p = 0,045), and the active role of the family (p = 0,000) with the suitability of balanced nutrition practices in the elderly. The results of this study also showed, there are no relationships between sex (p = 0,962), nutritional knowledge (p = 0,051), nutritional attitude (p = 0,429), health facilities and infrastructure (p = 0,192) with the suitability of balanced nutrition practices in the Sambiroto District, Semarang City. The results of multiple linear regression tests showed that the factor most related to the suitability of balanced nutrition practices is the active role of the family (p = 0,013, coefficient B = 0,293). The results of the simultaneous f test (p = 0,008) showed that the independent variables simultaneously affected the dependent variable. R square of 0,221 indicates that the ability of the independent variables in explaining the dependent variable is 22.1%.. It is recommended that health workers and volunteer cadres in Sambiroto District provide education with the target of families who have elderly people (elderly caregiver), especially related to elderly nutrition based on 10 Balanced Nutrition Messages.